2016
DOI: 10.1177/2158244016671376
|View full text |Cite
|
Sign up to set email alerts
|

Being In-Between

Abstract: Many persons with leg amputations experience that using a prosthesis enriches their quality of life. However, there is an ongoing concern with underuse and non-use of artificial limbs in lower limb prosthetic rehabilitation. Studies have identified an initial critical stage among potential prosthetic users. The aim of this study was to explore the lived experience of becoming a prosthetic user as seen from the perspective of patients. The study is based on the phenomenological framework of Reflective Lifeworld… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 38 publications
1
14
0
Order By: Relevance
“…These are in line with findings from previous studies that amputation particularly major amputation-related physical impairments bring challenges to patients' self-identity and amputees' expected return to normality (Hamill et al, 2010;Senra et al, 2012;Ostler et al, 2014). In particular, prosthesis gave them a sense of normality and made their hope of walking again a real possibility (Norlyk et al, 2016) and the expectation of returning normality appeared to be an important coping mechanism (Ostler et al, 2014). These have been also described by a participant with below-knee amputation in the present study who was extremely depressive immediately after amputation until he found prosthesis as his hope and new possibility to walk again as he expressed that 'I'm looking forward to have my prosthetic leg'.…”
Section: Struggling For Wound Healing and Normalitysupporting
confidence: 90%
See 2 more Smart Citations
“…These are in line with findings from previous studies that amputation particularly major amputation-related physical impairments bring challenges to patients' self-identity and amputees' expected return to normality (Hamill et al, 2010;Senra et al, 2012;Ostler et al, 2014). In particular, prosthesis gave them a sense of normality and made their hope of walking again a real possibility (Norlyk et al, 2016) and the expectation of returning normality appeared to be an important coping mechanism (Ostler et al, 2014). These have been also described by a participant with below-knee amputation in the present study who was extremely depressive immediately after amputation until he found prosthesis as his hope and new possibility to walk again as he expressed that 'I'm looking forward to have my prosthetic leg'.…”
Section: Struggling For Wound Healing and Normalitysupporting
confidence: 90%
“…Many studies have explored body image disturbance (Senra et al, 2012;Norlyk et al, 2013;McDonald et al, 2014;Norlyk et al, 2016;Khan et al, 2019) and changed self-identify for patients who have undergone major amputations. In the present study, we found that body image and anxiety was a concern for the participants with both major and minor amputation.…”
Section: Social Awareness and Support To Regain Normalitymentioning
confidence: 99%
See 1 more Smart Citation
“…Arman et al, 2008; Fjelland & Gjengedal, 2008; Norlyk, Martinsen, Hall & Haahr, 2016; Van Wijngaarden, Leget & Goossensen, 2015, 2016), patients have a desire to be seen and recognized as individuals in their personal context. They certainly do not want to be reduced to diagnoses, symptoms or to other parts of their being, but they need tools to address the disconnectedness caused by illness (cf.…”
Section: Conclusive Reflectionsmentioning
confidence: 99%
“…They certainly do not want to be reduced to diagnoses, symptoms or to other parts of their being, but they need tools to address the disconnectedness caused by illness (cf. Van Wijngaarden et al, 2016) or by treatment (Norlyk et al, 2016). Patients need care that addresses them as persons that belong to, but are not reducible to, a world characterized by social, cultural and natural relationships (cf.…”
Section: Conclusive Reflectionsmentioning
confidence: 99%